Long-Term Lateral Semicircular Canal Function in Children with Cochlear Implants: Results of Video Head Impulse Test - Nader Nassif; Cristiano Balzanelli; Luca Oscar Redaelli de Zinis (MDPI AG, 2021)
In children with profound deafness, bilateral cochlear implant (CI) is an effective, established procedure. However, its safety on vestibular function has recently been debated. The goal of this study is to evaluate the long-term lateral semicircular canal high-frequency vestibulo-oculomotor reflex (LSC HF VOR) in children with CI by video head impulse testing (vHIT). This is a cross-sectional study assessing a cohort of children who received either a unilateral (12) or a bilateral (12) cochlear implant (CI), compared with a control group of 12 normal-hearing children. No significant LSC HF VOR gain difference was found between CI users and controls. In the unilaterally implanted group, the LSC HF VOR gain measured in the "CI-ON" condition was significantly higher than in the "CI-OFF" condition, both in the implanted and in the non-implanted ear. In the bilaterally implanted group, the difference between the two conditions was not significant. Our results do not show any impairment of LSC HF VOR function in children with CI compared to normal-hearing children in the long-term period. This suggests that both unilateral and simultaneous/sequential bilateral CI are procedures that do not impair HF LSC long-term function when analyzed by vHIT.